High Risk for Obstructive Sleep Apnea in Relation to Hypertension Among Southeast Asian Young Adults: Role of Obesity as an Effect Modifier - Pensuksan, Wipawan C. (Oxford University Press, 2014)
BACKGROUND: Obstructive sleep apnea (OSA) has been linked to hypertension among middle-aged and older adults in Western countries. Few studies have focused on young adults, especially those in Southeast Asian countries undergoing epidemiologic transitions and experiencing elevated noncommunicable disease burden. We investigated associations of high risk for OSA with hypertension among Asian young adults. METHODS: A total of 2,911 college students in Thailand participated in this study. The high risk for OSA was assessed using the Berlin Questionnaire. Blood pressure (BP) and anthropometric measurements were taken by trained research staff. Elevated BP and hypertension were defined as BP ≥120/80mm Hg and ≥140/90mm Hg, respectively. Multivariable logistic regression models were fit to estimate odds ratios (ORs) and 95% confidence intervals (CIs) of elevated BP and hypertension. Stratified analyses were conducted to examine whether observed associations varied by weight status. RESULTS: High risk for OSA was significantly associated with elevated BP (OR = 2.38; 95% CI = 1.68–3.39) and hypertension (OR = 2.55; 95% CI = 1.57–4.15) after adjustment for demographic and lifestyle factors. When body mass index was further controlled for, observed associations were greatly attenuated. The associations were only evident among overweight and obese students. CONCLUSIONS: The high risk for OSA among overweight and obese young adults is associated with elevated BP and hypertension. Enhanced efforts directed toward screening and diagnosing OSA and weight control among young adults could be one strategy for improving cardiovascular health.